Những câu hỏi liên quan
SD
Xem chi tiết
BY
1 tháng 4 2016 lúc 20:17

2008-1/2008=2007/2008

1/2-1/2009=2007/2009

Bình luận (0)
TL
Xem chi tiết
PH
Xem chi tiết
DH
21 tháng 1 2022 lúc 15:52

\(B=2008+\frac{2007}{2}+\frac{2006}{3}+\frac{2005}{4}+...+\frac{2}{2007}+\frac{1}{2008}\)

\(=1+1+\frac{2007}{2}+1+\frac{2006}{3}+...+1+\frac{1}{2008}\)

\(=\frac{2009}{2009}+\frac{2009}{2}+\frac{2009}{3}+...+\frac{2009}{2008}\)

\(=2009\left(\frac{1}{2}+\frac{1}{3}+...+\frac{1}{2008}+\frac{1}{2009}\right)\)

Suy ra \(A=2009\).

Bình luận (0)
 Khách vãng lai đã xóa
HH
Xem chi tiết
NL
Xem chi tiết
VT
Xem chi tiết
TL
15 tháng 3 2017 lúc 10:27

2009 nha

Bình luận (0)
LZ
15 tháng 3 2017 lúc 10:51

2009 ???

-_-

Bình luận (0)
CD
15 tháng 3 2017 lúc 11:20

 2009 chuẩn 100000% luôn

Bình luận (0)
NK
Xem chi tiết
TD
23 tháng 10 2016 lúc 20:47

Gọi a là tử số, b là mẫu số của phân số A

a = \(\frac{2008}{1}\)\(\frac{2007}{2}\)\(\frac{2006}{3}\)+ ... + \(\frac{1}{2008}\)

Dãy số a có (2008 - 1)  : 1 + 1 = 2008 số. Và a = ( \(\frac{2008}{1}\)\(\frac{1}{2008}\)) x (2008 : 2) 

b = \(\frac{1}{2}\)\(\frac{1}{3}\)\(\frac{1}{4}\)+ ... + \(\frac{1}{2009}\)

Dãy số b có (2009 - 2) : 1 + 1 = 2008 số. Và b = (\(\frac{1}{2}\)\(\frac{1}{2009}\)) x (2008 : 2)

A = [ ( \(\frac{2008}{1}\)\(\frac{1}{2008}\)) x (2008 : 2)] : [ (\(\frac{1}{2}\)\(\frac{1}{2009}\)) x (2008 : 2)] = ( \(\frac{2008}{1}\)\(\frac{1}{2008}\)) :  (\(\frac{1}{2}\)\(\frac{1}{2009}\)

A = \(\frac{\text{2008 x2008 + 1}}{2008}\)\(\frac{2x2009+2}{2x2009}\)

A = 2008

Bình luận (0)
SX
Xem chi tiết
NT
29 tháng 3 2015 lúc 14:48

\(A=\frac{2008+\frac{2007}{2}+\frac{2006}{3}+\frac{2005}{4}+...+\frac{2}{2007}+\frac{1}{2008}}{\frac{1}{2}+\frac{1}{3}+\frac{1}{4}+\frac{1}{5}+...+\frac{1}{2008}+\frac{1}{2009}}\)

\(=\frac{\left(1+\frac{2007}{2}\right)+\left(1+\frac{2006}{3}\right)+\left(1+\frac{2005}{4}\right)+...+\left(1+\frac{1}{2007}\right)+\left(1+\frac{1}{2008}\right)+1}{\frac{1}{2}+\frac{1}{3}+\frac{1}{4}+\frac{1}{5}+...+\frac{1}{2008}+\frac{1}{2009}}\)

\(=\frac{\frac{2009}{2}+\frac{2009}{3}+\frac{2009}{4}+...+\frac{2009}{2007}+\frac{2009}{2008}+\frac{2009}{2009}}{\frac{1}{2}+\frac{1}{3}+\frac{1}{4}+\frac{1}{5}+...+\frac{1}{2008}+\frac{1}{2009}}\)

\(=\frac{2009\left(\frac{1}{2}+\frac{1}{3}+\frac{1}{4}+\frac{1}{5}+...+\frac{1}{2008}+\frac{1}{2009}\right)}{\frac{1}{2}+\frac{1}{3}+\frac{1}{4}+\frac{1}{5}+...+\frac{1}{2008}+\frac{1}{2009}}=2009\)

Bình luận (0)
NN
Xem chi tiết
H24
22 tháng 3 2016 lúc 11:20

$=\frac{2008+\frac{2007}{2}+\frac{2006}{3}+\frac{2005}{4}+...+\frac{2}{2007}+\frac{1}{2008}}{\frac{1}{2}+\frac{1}{3}+\frac{1}{4}+\frac{1}{5}+...+\frac{1}{2008}+\frac{1}{2009}}$

$1+\left(1+\frac{2007}{2}\right)+\left(1+\frac{2006}{3}\right)+...+\left(1+\frac{1}{2008}\right)$

$\frac{2009}{2009}+\frac{2009}{2}+\frac{2009}{3}+...+\frac{2009}{2008}$

$2009.\left(\frac{1}{2}+\frac{1}{3}+\frac{1}{4}+...+\frac{1}{2009}\right)$

A=$\frac{2009.\left(\frac{1}{2}+\frac{1}{3}+\frac{1}{4}+...+\frac{1}{2009}\right)}{\frac{1}{2}+\frac{1}{3}+\frac{1}{4}+...+\frac{1}{2009}}$

A=2009

Bình luận (0)
H24
22 tháng 3 2016 lúc 11:20

bằng 2009 nha 

Bình luận (0)